2006
DOI: 10.1080/00313830600953576
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Number Sense in China and Finland

Abstract: This study examined the influence of nationality, age and gender on Chinese (N5130) and Finnish (N5203) pre-schoolers' number sense. Two highly correlated aspects of number sense were extracted: one reflecting the children's ability to organise and compare quantities (i.e. relational skills), and another pertaining to their ability to operate with number-word sequence (i.e. counting skills). The results showed a significant age-related gain in both aspects of number sense, whereas no gender differences were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 30 publications
2
55
2
3
Order By: Relevance
“…For example, it has been argued that by age four or five children have normally acquired initial counting skills and an awareness of quantity that allows them to respond to questions about more or less, while by the time they start school children have typically acquired a sense of a mental number line (Aunio et al 2006;Griffin 2004). However, such number-related understandings are frequently dependent on individual family circumstances (Zur and Gelman 2004), indicating that instruction, whether implicit or explicit, may be necessary for their development.…”
Section: What Is Number Sense?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been argued that by age four or five children have normally acquired initial counting skills and an awareness of quantity that allows them to respond to questions about more or less, while by the time they start school children have typically acquired a sense of a mental number line (Aunio et al 2006;Griffin 2004). However, such number-related understandings are frequently dependent on individual family circumstances (Zur and Gelman 2004), indicating that instruction, whether implicit or explicit, may be necessary for their development.…”
Section: What Is Number Sense?mentioning
confidence: 99%
“…So, what are the characteristics of FONS? Broadly speaking it has been described as the ability to operate flexibly with number and quantity (Aunio et al 2006;Clarke and Shinn 2004;Gersten and Chard 1999) and can be expressed as attributes like "awareness, intuition, recognition, knowledge, skill, ability, desire, feel, expectation, process, conceptual structure, or mental number line" (Berch 2005, p. 333). Despite such vagueness, some scholars have tried to categorise its characteristic properties.…”
Section: A Tentative But Concise Characterisation Of Foundational Nummentioning
confidence: 99%
“…Aunio, Niemivirta, et al 2006; have shown that, the ENT also provides two closely related subscales measuring slightly different aspects of children's early numeracy. The first four sections of the instrument relate to the logical principles often identified as the key factors underlying children's understanding of quantities and relations (i.e.…”
Section: Instrumentsmentioning
confidence: 99%
“…Another set of cross-cultural comparisons on early numeracy have been conducted with Finnish and Chinese children (Aunio, Niemivirta et al 2006), children from Finland, Hong Kong and Singapore (Aunio et al 2004) and children from China, Finland, and Singapore (Ee, Wong, and Aunio 2006).…”
Section: Cross-national Differences In Mathematical Skillsmentioning
confidence: 99%
“…According to number sense performance, there are statistically no significant difference between male and female preservice mathematics teachers [t (462) = 4.115, p> .05, ƞ 2 = 0.04]. Earlier studies (Aunio et al 2006;Harç, 2010;Kayhan-Altay, 2010;Menon, 2004; Consequently, this study shows that pre-service mathematics teachers do not perform well at using number sense based strategies. Yang et al (2009) stated that "If we want to improve students' number sense, then action should be taken to improve the quality of their teachers' knowledge on number sense.…”
Section: An Investigation Of Pre-service Elementary and Secondary Matmentioning
confidence: 88%